Building Strong Foundations, Educational Management's Contribution To Character Education And Graduate Quality Enhancement - Sanjani, M. Aqil Fahmi; Islamiah, Robitotul; Maulidiah, Linda (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to discuss educational management's role in improving graduates' quality through character education at MA Al Qodiri Jember and MBI Amantul Ummah Pacet Mojokerto. The discussion reveals the concepts and implications of the role of educational management in the context of two Islamic boarding school-based schools using multi-site qualitative research methods. Data was obtained through closed interviews, documentation, and discussion forums to fulfill the research, and then the data was analyzed through triangulation. Educational management at both schools plays a crucial role in emphasizing student character formation. Developing a curriculum oriented towards character education and implementing character education programs is the main focus in producing graduates who are academically superior and have good character. With a directed and integrated approach, MA Al Qodiri Jember and MBI Amantul Ummah Pacet Mojokerto emphasized that character education is not just an addition but the essence of education itself, which forms quality individuals who are ready to contribute positively to society. This research underlines the importance of character education in forming a young generation who is solid and responsible in facing future challenges.